Preoperative diagnosis of parathyroid cysts: Examination of fluid obtained by cytological puncture - Paseyro De Morelli, Ana; Iraola, Luz; Maggiolo, Jorge; A. Gregorio, Luis; Paseyro, Pedro (Cirugía del Uruguay, 1971)
Preoperatory diagnosis of clinically significant parathyroid cysts has been possib!e through physical, chemical, immunological, and cytological examination of the fluid obtained by fine needle aspiration puncture of the cysts. Cystic fluid is colorless. Immunological tests for thyroglobulin were consistently negative. No spontaneous coagulation was observed. Upon cytological examination only a few desquamation cell debris were found after centrifugation of the specimen. Standard chemical determinations were performed. Over a 11 year period, 18 cases have been studied: 9 were operated upon histologic diagnosis of parathyroid cysts been accomplished in all of them. The test employed enables the differential diagnosis between parathyroid cysts and cysts of thyroid origin, lymphangiomata, branchial and hydatid cysts.